Relasi Rasm dan Ilmu Tajwid di Indonesia: Analisis Catatan Penulisan Rasm pada Mushaf Kuno Kusamba - Fais, Nor Lutfi; Murtaza MZ, Ahmad; Sanabila Alfian N.H., Moh. (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
The study results on rasm (script) of ancient manuscripts indicate that only a few manuscripts adhere to the rules of Uthmani rasm. Among these limited manuscripts, the selection of Uthmani rasm rules differs from what is commonly chosen today, namely the riwayah (transmissions) of Abu 'Amr ad-Dani and Abu Dawud Sulaiman, along with their works in the field of rasm, Al-Muqni' and At-Tabyin. This study attempts to analyze the references of the application of the Uthmani rasm in the ancient manuscript of Kampung Kusamba, Bali. Such studies are crucial for understanding the landscape of rasm studies during specific eras in the past, especially in light of claims of the negligible use of the Uthmani rasm since the 4th century of the Hijri calendar. Utilizing codicological, historical, and scriptural perspectives, the application of Uthmani rasm in the ancient manuscript of Kampung Kusamba, Bali refers to the text of Manar al-Huda. The chosen reference provides an explanation of how the rules of Uthmani rasm can be consistently applied in ancient manuscripts while also indicating a strong relationship between rasm studies and the science of tajwid.